2015
DOI: 10.1155/2015/325652
|View full text |Cite
|
Sign up to set email alerts
|

Safety of Allogeneic Umbilical Cord Blood Stem Cells Therapy in Patients with Severe Cerebral Palsy: A Retrospective Study

Abstract: This retrospective study aimed to assess the safety of patients with severe cerebral palsy (CP), who received allogeneic umbilical cord blood stem cells (UCBSCs) treatment from August 2009 to December 2012 in Guangdong Provincial Hospital of Chinese Medicine. A total of 47 patients with average age of 5.85 ± 6.12 years were evaluated in this study. There was no significant association with allogeneic UCBSCs treatments found in the data of the laboratory index . No casualties occurred. Some adverse events durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(48 citation statements)
references
References 25 publications
3
45
0
Order By: Relevance
“…34,35 Some follow-up safety data are becoming available. 36 Despite this recent progress, designing cell therapy studies remains challenging, and ethical concerns need to be addressed. Most of the data available to date originate from various parts of the world, and integrating the various regulatory and research methodology approaches remains a future challenge.…”
Section: New Therapeutic Resources and Researchmentioning
confidence: 99%
“…34,35 Some follow-up safety data are becoming available. 36 Despite this recent progress, designing cell therapy studies remains challenging, and ethical concerns need to be addressed. Most of the data available to date originate from various parts of the world, and integrating the various regulatory and research methodology approaches remains a future challenge.…”
Section: New Therapeutic Resources and Researchmentioning
confidence: 99%
“…There is currently no specific treatment for CP except for rehabilitation training in the clinic (Maclennan et al, ). Since the first transplantation of UCBCs was performed in 1988 (Mreboredo, Diaz, Castro, & Villaescusa, ), UCB‐SC therapy has been widely studied in children with CP, and improved brain cognition and gross motor function have been shown with no serious side effects indicating that the therapy is neuroprotective and safe (Feng et al, ; Huang et al, ; Kang et al, ; Lee et al, ; Min et al, ; Romanov et al, ; Sun et al, ) (Table ). However, current clinical trials focused on UCB‐SC therapy in children with CP have not considered the gestational age partition of the patients, and thus further research is needed regarding children with CP who were born prematurely.…”
Section: Ucb‐sc Therapy In Preterm Brain Injuries and Neurological Sementioning
confidence: 99%
“…Clinical trials have demonstrated the safety of UCB administration to children with established CP (Lee et al, 2012; Feng et al, 2015; Novak et al, 2016). Currently, however, it remains unclear how effective UCB could be in the setting of chorioamnionitis and preterm birth.…”
Section: Stem Cell Therapiesmentioning
confidence: 99%